1999
DOI: 10.1161/01.cir.99.6.736
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Low HDL on Progression of Coronary Artery Disease and Response to Fluvastatin Therapy

Abstract: Background —Patients with coronary artery disease (CAD) commonly have low HDL cholesterol (HDL-C) and mildly elevated LDL cholesterol (LDL-C), leading to uncertainty as to whether the appropriate goal of therapy should be lowering LDL-C or raising HDL-C. Methods and Results —Patients in the Lipoprotein and Coronary Atherosclerosis Study (LCAS) had mildly to moderately elevated LDL-C; many also had low HDL-C, providing an opportunity to compare angiograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
84
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 193 publications
(92 citation statements)
references
References 34 publications
7
84
0
1
Order By: Relevance
“…30 Finally, patients with low HDL-C benefitted most when treated with fluvastatin in the Lipoprotein and Coronary Atherosclerosis Study (LCAS). 31 No association was seen between changes in plasma lipids during statin therapy and individual SNPs, supporting our findings that the interaction of multiple CETP SNPs within a haplotype is a more powerful determinant of the clinical phenotype than are individual SNPs. This has also been demonstrated for the b2-adrenergic receptor and the response to a b2-bronchodilator.…”
Section: Discussionsupporting
confidence: 80%
“…30 Finally, patients with low HDL-C benefitted most when treated with fluvastatin in the Lipoprotein and Coronary Atherosclerosis Study (LCAS). 31 No association was seen between changes in plasma lipids during statin therapy and individual SNPs, supporting our findings that the interaction of multiple CETP SNPs within a haplotype is a more powerful determinant of the clinical phenotype than are individual SNPs. This has also been demonstrated for the b2-adrenergic receptor and the response to a b2-bronchodilator.…”
Section: Discussionsupporting
confidence: 80%
“…[1][2][3] Lipid lowering with statins in patients with elevated LDL improves, but does not normalize, endothelial vasomotor function. [27,35] Although the use of this class of medication markedly reduces clinical cardiovascular events, the majority of CAD events are not prevented in statin-treated patients. [14][15][16][17][18] Low levels of HDL increase the risk of the development of CAD, whereas high HDL levels are protective against this disease.…”
Section: Discussionmentioning
confidence: 99%
“…Khadem-Ansari et al 20 reported that the history of familial CHD was 27.3% of their CAD patients. Senaratne et al 32 35 found that more significant coronary artery lesions associated with low HDL-C patients (77.0%), Ballantyne et al 36 found that percentage of diameter stenosis was more in low HDL-C patients. Rahman et al 37 found low HDL-C associated with large lesions.…”
Section: Materials and Methodmentioning
confidence: 98%